English Learners’ Perspective on Using ‘It Takes Two’ Video Game in Acquiring English Vocabulary - Nurchumayrah, Zalsa Auliya; Talib, Ahmad; Asriati, Asriati (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2025)
The purpose of this research is to investigate how English learners’ perspective on the use of ‘It Takes Two’ video game as a tool for acquiring vocabulary. This research uses a qualitative method with a case study approach. The population of this research was English language learners in the It Takes Two community located in Makassar. Data were collected through in-depth interviews with four English language learners who meet the sampling criteria. The research found that the use of this video game increases motivation to learn English, enriches vocabulary, and helps vocabulary comprehension through supporting visual and audio displays. Although the results of this research show a positive impact, this research has limitations in terms of the number of participants and the relatively short duration of the research. Therefore, longitudinal studies with larger participants are also recommended to gain more comprehensive insights into the long-term effectiveness of game-based learning.